THE MOTIF OF DREAMS IN KARAKALPAK FOLK EPICS - Kulimbetova Aysholpan Kuatbayevna (KONFERENSIYALAR, 2025)
Annotation. This article analyzes the peculiarities of the emergence and application of the dream motif in Karakalpak folk epics. The research studies the mythological and historical roots of the  dream  motif  and  reveals  its  role  in  the  development  of  the  epics’  plot.  The  research  results demonstrate  the  unique  characteristics  of  the  dream  motif  in  Karakalpak  folk  epics  and  its connection with the worldview and beliefs of the people.